JEJAK BAHASA PROTO-AUSTRONESIA PADA PRASASTI GUNUNG TUA (LOKANĀTHA) - Mulyadi; Churmatin Nasoichah; Dwi Widayati (Balai Arkeologi Kalimantan Selatan, 2021)
The problem of this research is how the PAN traces at the phonological, morphological, and syntactic levels on the Gunung Tua Inscription (Lokanātha). The purpose of this study was to determine the PAN traces at the phonological, morphological, and syntactic levels of the inscription. The method used is descriptive qualitative method. Based on the analysis carried out on that inscription, it is known that at the phonological level there are two words, namely /juru/ 'clever person' and /pāṇḍai/ 'clever, skilled’. The word /juru/ 'clever person' is a loan word from Sanskrit while the word /pāṇḍai/ 'clever, skilled' has the form PAN */paṇḍai/ 'clever, skilled'. Based on the morphological level, there are two words, namely barbwat 'making' and tatkāla 'when'. The word barbwat is formed from the free morpheme bwat 'make' and the second bar- bound morpheme is a PAN derivative. Meanwhile tatkāla 'when' is not a derivative of PAN but a loan word from Sanskrit which consists of two morphemes, namely tāt 'so' and kālá 'time' so that it becomes tātkālá. Based on the syntactic level, it can be concluded that BMK has a grammatical structure consisting of FAdv as adverb of time, FN as subject and object, and FV as predicate that are transitive in form.